The Concept of the Oneness of God in the Geguritan Krama Selam Text As Reinforcement of Religious Moderation - I Kadek Widiantana (IAHN-TP Palangka Raya, 2022)
Balinese literature in terms of content is divided into Purwa Balinese Literature and Anyar Balinese Literature. Geguritan is a part of Purwa Balinese Literature. Geguritan cannot be separated from stories, traditions, or Hindu religious values. But one of them, there is a Geguritan containing Islamic teachings which is a unique one. This is certainly interesting to study, especially in terms of content analysis methods and literary reception theory. Based on the analysis conducted, Geguritan Krama Selam teaches the concept of the oneness of God, how the mention of the names Hyang Widi and Allah is used interchangeably and also it is said that Hyang Widi and Allah are one. Understanding the oneness of God will indirectly avoid blaspheming, harassing, or insulting the beliefs of other people who do not share the same faith because in fact all come from one source.